Kinetics and Mechanisms of the Reactions of Iodopentaam-mineruthenium(III) and Thiocyanate Ions in Aqueous Solution - Prasad, Rameshwar; Singh, B.K.; Chaurasia, P.K.; Kumar, Sanjay (Asian Journal of Chemistry, 2010)
Investigations were carried out on the substitution of iodide ionby thiocyanate ion on iodopentaammineruthenium(III) ion in thetemperature range 35-50°C. Rate increases linearly with SCN-. Aplot of 'K' vs. SCN- shows positive intercept on rate axis, indicatingboth SCN- dependent and SCN- independent pathways for thesubstitution reaction. Substitution of SCN- on aquapentaamminecomplex has also been investigated to make a comparative studyof the two reactions. Both the reactions follow an associative interchangemechanism.